2021
DOI: 10.1001/jamasurg.2021.4568
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Drainage Tube Use for Preventing Anastomotic Leakage After Laparoscopic Low Anterior Resection in Patients With Rectal Cancer

Abstract: Preventing anastomotic leakage (AL) is crucial for colorectal surgery. Some studies have suggested a positive role of transanal drainage tubes (TDTs) in AL prevention after low anterior resection, but this finding is controversial.OBJECTIVE To assess the effect of TDTs in AL prevention after laparoscopic low anterior resection for rectal cancer. DESIGN, SETTING, AND PARTICIPANTSThis multicenter randomized clinical trial with parallel groups (TDT vs non-TDT) was performed from February 26, 2016, to September 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 70 publications
0
48
0
Order By: Relevance
“…Among the measures to treat anastomotic leakage, drainage is consistent, and its effect determines the development of the disease. 20–22 If the drainage effect is good, some patients can be exempted from receiving secondary diversion surgery, thus preserving anal function. The drainage path can be through the pelvis, through the anus, and through both the pelvis and anus.…”
Section: Discussionmentioning
confidence: 99%
“…Among the measures to treat anastomotic leakage, drainage is consistent, and its effect determines the development of the disease. 20–22 If the drainage effect is good, some patients can be exempted from receiving secondary diversion surgery, thus preserving anal function. The drainage path can be through the pelvis, through the anus, and through both the pelvis and anus.…”
Section: Discussionmentioning
confidence: 99%
“…The placement of the stent can allow the perforation to heal in an appropriate manner, which can effectively reduce the possibility of scarring and stenosis. Another advantage of the stent is that it can effectively prevent the development of a proximal intestinal diversion stoma[ 15 - 19 ]. TIDTs with balloons have a very good therapeutic effect in the prevention and treatment of anastomotic leakage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to stent therapy, studies have shown that TIDTs, which are placed 3-5 cm above the anastomosis, can be used to prevent anastomotic leakage after rectal cancer resection[ 14 , 18 ], and some studies have shown that anastomotic leakage cannot be prevented[ 19 ]. After the intestinal cavity is sealed by the balloon, artificial intestinal obstruction may occur, which easily promotes intestinal peristalsis, and the TIDTs are easily discharged.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the use of a transanastomotic drainage tube (TDT) may be useful in preventing the onset of AL. Regarding the TDT, several studies showed no difference in AL rate between patients with and without one[ 31 ]. Other literature observations, instead, have documented a reduction in frequency of AL in patients with TDT[ 32 - 35 ].…”
Section: To the Editormentioning
confidence: 99%